Applied Photoelasticity for Residual Stress Measurement inside Crystal Silicon Wafers for Solar Applications. (23rd May 2016) - Jagailloux, F.; Valle, V.; Dupré, J.‐C.; Penot, J.‐D.; Chabli, A.
Abstract: A full automated NIR polariscope has been specially built for residual stress measurement in crystal silicon wafers for solar applications. The multiple configurations of the instrument allow measuring both the isoclinic and the isochromatic parameters on a full field. A new algorithm has also been developed to extract the maximal shear stress inside the silicon wafers without linking the isoclinic parameter to the isochromatic parameter. Hence, it is straightforward to use and the extraction errors are reduced. Coupling this improved data analysis with the comprehensive capabilities of the test rig, allowed to show that the effect of the cutting process on the residual stress inside the silicon wafers is predominant compared with the effect of the cast process, related to the thermal gradient and impurities.